FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA PADA KARYAWAN UNIT PELAYANAN TEKNIK DI PT. PLN BANGKINANG KOTA - Ade Dita Puteri; Susi Afrianti (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
Work accident is an unexpected and undesirable event that disrupts the activities of workers at work, causing harm to workers and the company. Some of the factors that cause workplace accidents include Work Period, use of PPE and Behavior. The purpose of this study was to determine the factors associated with workplace accidents in Engineering Services Unit employees at PT. PLN Bangkinang City. Design quantitative analytic research with cross sectional design. The sample in this study amounted to 45 people. The sampling technique is total sampling using a questionnaire. This research was conducted on 6-12 September 2018 at PT. PLN Bangkinang City. The data obtained were analyzed by Fisher's Exact Test with a significance level of 95%. Based on the results of the study showed that there was a significant relationship between work period and work accident as evidenced by the p value (0.002)